RISK FACTORS OF GUM RECESSION IN PATIENTS OF DIFFERENT AGE GROUPS - Umarova Odinakhon Numanovna (Scholar Express Journal, 2022)
This article discusses the analysis of risk factors affecting the occurrence of gingival recession in patients of different age groups. Aclinical examination was carried out in 64 patients with gingival recession, aged 18 to 75 years, who were divided into age groups. As a result of taking into account the constitutional features of the periodontal tissues and factors of the occurrence of gum recession and timely elimination of these factors, will reduce the risk of a recession.
Keywords: Gum Recession; Periodontium; Hygiene Index